Pengaruh Citra Merek Dan Kualitas Produk Terhadap Minat Beli Konsumen Dengan Word Of Mouth Sebagai Variabel Intervening Pada Parfum Azzwars Kota Padang - Afdal, Afdal (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to find out how much influence Product Quality and Brand Image have on Purchase Interest with Word of Mouth as an Intervening Variable. The population used in this research were consumers of Azzwars Perfume in Padang City, Simpang Haru branch. The sampling technique used was purposive sampling, and 72 respondents were obtained as samples. The data collection method was obtained through distributing questionnaires directly. The analytical method used is Multiple Linear Regression Analysis. The analytical tool used is SPSS 25. The results of this research show that brand image and product quality partially have a positive and significant effect on word of mouth. Brand image, product quality and word of mouth partially have a positive and significant effect on consumer purchase interest. Word of Mouth as an intervening variable is unable to mediate the influence of brand image and product quality on consumer purchasing interest